Antecedents of Thai student teacher sustainable consumption behavior - Paitoon Pimdee (My University, 2020)
A new area of research and intervention has arisen, namely the psychology of sustainability. Therefore, this study investigates how an undergraduate student teacher's psychological traits, their psychological state, their situation, and environmental education affect their sustainable consumption behavior. Two sample groups were selected from ten Thai university education programs' science (n = 400) and social science (n = 400) colleges nationwide. The research instrument used randomized multistage questionnaires for each group, which used a five-level scale to evaluate each student teacher's item agreement. The analysis of the causal relationship models used LISREL 9.10 which determined that both models and their four causal variables positively affected a Thai student teacher's sustainable consumption behavior (SCB). For the science education student teachers, these were the situation (SIT = 0.87), environmental education (EDU = 0.34), their psychological state (STATE = 0.22), and their psychological traits (TRAITS = 0.22). For the social science education student teachers, these were SIT = 0.85, STATE = 0.25, EDU = 0.08, and TRAITS = 0.04. Combined, they can explain 92% (science program) and 82% (social science program) of variance in a student teacher's SCB. The study also determined that EDU's attitude and conservation factors were critical, which most probably increased in prominence due to media awareness efforts. There also appears to be greater individual responsibility in SCB as well as the perceived need to conserve resources. Finally, this study further confirmed numerous other studies in which humans have a strong desire to fit in and will conform to the behavior of those around them, with this study concluding that each student teacher's situation was determined to have a moderate to strong influence on either their psychological state or environmental education. This study contributed to the literature as it investigated 18 aspects related to four casual variables affecting a Thai student teacher's sustainable consumption behavior. The study was unique in that it classified and compared opinions from two diverse university teaching programs nationwide (Science and Social Science), whose results can help educational leaders identify and develop in-depth, SCB future programs.
Keywords: Consumption; Sustainable Consumption; Environmental Education and Sustainability